Pengaruh Konsentrasi Ethepon dan Jenis Kemasan terhadap Kualitas Buah Pisang Janten (Musa eumusa ABB Group) - Fizzaria Khasbullah; Qori Inar Ratul Ulya; Yatmin Yatmin; Rakhmiati Rakhmiati (J-Plantasimbiosa, 2024)
This study aims to determine the effect of various Ethepon concentrations and the right type of packaging for the quality of Janten bananas, and the interaction of both. The method used, the experimental method, with a completely randomized block design (RBD) arranged in factorial : (1) ethephone concentration(e) There are 3 types; (e0)without ethepon or 0 ml; (e1)2 mL/L or 30mL/15 L water; (e2)4 mL/L or 60mL/15L water. (2) packaging section (k) There are 3 types; (k1)plastic, (k2)cardboard, and (k3)gunny sacks. Observational data were tested with the Least Significant Difference test (LSDT, at the 5%. The results showed that: The administration of Ethepon at various concentrations had an effect on the quality of Janten bananas, as seen in the variable color, aroma, taste, level of hardness, level of sweetness, vitamin C and total dissolved acid except for the weight loss variable. The best Ethepon concentration is 4mL/L or 60mL/L Ethepon. The use of packaging has an influence on the quality of Janten bananas, which can be seen in the variables of color, aroma, taste and level of sweetness. The best packaging is cardboard packaging. There is an interaction between different concentrations of Ethepon and packaging on the quality of Janten bananas.